Israeli Ceasefire Violations in Aljazeera’s Reporting: A Critical Discourse Analysis by Norman Fairclough - Shofiya Nur Azizah; Dien Nur Chotimah (Universitas Islam Negeri Palopo, 2025)
News is a very effective medium in conveying information, messages, and criticism due to its ability to attract wide attention. This study aims to analyze the linguistic aspects, discourse practices, and sociocultural practices in Al-Jazeera news discussing the ceasefire violations by Israel. This qualitative study uses two news items as data sources, collected through reading, sorting, and recording methods. The analysis was conducted using the Critical Discourse Analysis theory approach from Norman Fairclough's perspective. The results show that there are 18 data consisting of linguistic analysis, discourse analysis, and sociocultural analysis that overall convey strong criticism of the ceasefire violations by Israel. Through Norman Fairclough's critical discourse analysis, the study found that the news not only conveys facts but also constructs a critical ideological narrative using analysis of language dimensions, discourse practices, and sociocultural practices as a tool to convey socio-political messages.